1999
DOI: 10.1089/107999099313226
|View full text |Cite
|
Sign up to set email alerts
|

IFN-alpha Receptor mRNA Expression in a United States Sample with Predominantly Genotype 1a/I Chronic Hepatitis C Liver Biopsies Correlates with Response to IFN Therapy

Abstract: Our aim was to assess whether, in the United States, with the predominant hepatitis C viral (HCV) genotypes 1a/I and 1b/II, hepatic interferon-alpha receptor (IFNAR) mRNA expression correlated with response to IFN therapy, levels of HCV RNA, or histologic activity index (HAI). Nine of 24 patients (38%) had an initial response to IFN treatment, 5 of whom (21%) had a sustained response. The corrected hepatic IFNAR mRNA expression (measured by RT-PCR) for the sustained responder group (mean +/- SE, 0.16 +/- 0.06,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
19
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 38 publications
2
19
2
Order By: Relevance
“…The differences in IFNAR1-mRNA levels in PBMC between responders and non-responders before IFN-α therapy were similar to those observed in liver biopsies from HCVinfected patients (14,17). It is likely that IFNAR1-mRNA expression in PBMC reflects the IFNAR1-mRNA status of the liver, as recently demonstrated for IFNAR2 (18).…”
supporting
confidence: 81%
See 2 more Smart Citations
“…The differences in IFNAR1-mRNA levels in PBMC between responders and non-responders before IFN-α therapy were similar to those observed in liver biopsies from HCVinfected patients (14,17). It is likely that IFNAR1-mRNA expression in PBMC reflects the IFNAR1-mRNA status of the liver, as recently demonstrated for IFNAR2 (18).…”
supporting
confidence: 81%
“…Non-responders Controls the liver (13,14,17). Moreover, IFNARmRNA levels in liver were not correlated with serum ALT or 2',5'-oligoadenylate synthetase levels, viral load or HCV (11,17).…”
Section: Respondersmentioning
confidence: 89%
See 1 more Smart Citation
“…634,2000). Other studies have demonstrated that the IFN-␣/␤ receptor is down-regulated in HCV chronically infected patients (25,26,46). The importance of the host in IFN responsiveness was also demonstrated when the virus from an IFNunresponsive patient became responsive to IFN when transmitted to another individual (58).…”
Section: Resultsmentioning
confidence: 97%
“…Accordingly, the expression levels of various types of IFN receptor subunit genes and their ratios may have an infl uence on the levels of type I IFN-mediated signals and, thus, an association with IFN response. Several studies have suggested that in CH-C, high levels of IFNAR1 or IFNAR2 mRNA in the liver are related to a sustained virological response [5][6][7][8][9] , but no information is available on the infl uence of spliced variant forms of IFNAR2 on the effi cacy of IFN therapy. Furthermore, a recent study has reported confl icting results about the importance of IFNAR1 and IFNAR2 mRNA on response to IFN therapy [10] .…”
mentioning
confidence: 99%